Linguistic Interference in Reading Stroop Card - Upadhayay, N.; Guragain, S.; Khadka, P. (Kathmandu University Medical Journal, 2022)
Background The Stroop test is a gold-standard cognitive function test that assesses selective attention. There are discrepancies of having language interaction in bilingual individuals on stroop test. Objective To assess selective attention of Nepalese in Nepali and English versions of stroop test and investigating gender differences in it. Method The study includes male (n 33) and female (n 33) of age 20-40 years. Their first home language is Nepali. The comparison of congruent and incongruent reaction time (selective attention) between two test versions was analyzed by Paired t-test. Gender differences on selective attention were analyzed by Independent sample t-test. Data are expressed as mean ± SD, p < 0.05. Result The congruent time in Nepali test (47.34 ± 9.23) was higher than English (42.21 ± 10.17) test. The selective attention in Nepali (113.11 ± 24.04) was significantly better (low latency) than English version (119.67 ± 28.81) of the test. Female outperformed male in selective attention on both the versions. Conclusion Orthographically and phonologically dissimilar languages affect the reaction time of bilingual individuals. Nepali stroop test can be a valid tool in assessing selective attention on Nepalese population. Females outperform males on selective attention as assessed by stroop test.